Stolen childhood taking a toll at young adulthood: The higher risk of high blood pressure and high blood glucose comorbidity among child brides - Biplab Datta; Ashwini Tiwari; Lynn Glenn (PLOS Global Public Health, 2022)
Despite notable progress being made in preventing child marriage, a significant proportion of women worldwide are still married before reaching adulthood. Though many aspects of child marriage have been widely studied, little is known on the later life health outcomes of child brides, let alone the critical need for healthcare during adulthood. This paper examines whether child brides at a young adult age bear a greater risk of high blood pressure (HBP) and high blood glucose (HBG) comorbidity than those who were married as adults. Using nationally representative data from India, we categorized married young adult (aged 20-34 years) women in four categories: neither HBP nor HBG, HBP only, HBG only, and both HBP and HBG. We estimated multinomial logistic regressions to obtain unadjusted and adjusted relative risk ratios in favor of these mutually exclusive outcomes for the child marriage indicator. Around 0.5% of the women in our sample had high blood pressure and high blood glucose comorbidity. While the prevalence of comorbidity was 0.4% among women who were married as adults, comorbidity was 40% higher (p < 0.000) among women who were married as children. The relative risk of the comorbidity among child brides was 1.4 (95%CI: 1.2–1.7) times that of their peers who were not married as children. The findings, thus, suggest that child brides at young adult age are at greater risk of having high blood pressure and high blood glucose comorbidity. Concerted public health efforts, therefore, are necessary to improve their long-term health and wellbeing.